Optimizing Sweet Corn Yield and Profitability Through NPK Compound Fertilizer Application - Furqoni, Hafith (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Sweet corn (Zea mays L. saccharata) is a high-value horticultural crop whose productivity is closely linked to effective nutrient management, particularly the balanced application of macronutrients—nitrogen (N), phosphorus (P), and potassium (K). This study evaluates the agronomic and economic impacts of applying NPK compound fertilizer at varying doses (0.5×, 0.75×, 1.0×, 1.25×, and 1.5× the recommended rate) on sweet corn growth and yield performance. Field experiments demonstrated that NPK application significantly enhanced vegetative growth parameters, including plant height, leaf number, and stem diameter, with improvements ranging from 15.8% to 37.3% over the unfertilized control. Yield components such as ear length, husked ear weight, and dehusked ear weight also showed marked increases, resulting in higher total yields per plot and per hectare. Among the treatments, the 1.25× dose achieved the highest relative agronomic effectiveness (RAE) at 147%, indicating superior nutrient utilization and biomass conversion. However, the 1.0× dose yielded the most favorable economic outcome, generating a net profit of Rp. 10,780,200 and an R/C ratio of 1.47, suggesting optimal cost-efficiency. These findings underscore the dual benefits of NPK compound fertilizer in sweet corn cultivation, highlighting that precise dosage not only maximizes agronomic performance but also enhances economic viability. The study recommends adopting the 1.0× dose for balanced productivity and profitability, while the 1.25× dose may be considered in contexts prioritizing yield maximization.